1995
DOI: 10.1143/jjap.34.187
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Properties and Structure of the Ba6-3xSm8+2xTi18O54 Solid Solutions

Abstract: The microwave dielectric properties of the Ba6-3 x Sm8+2 x Ti18O54 (0.3≤x≤0.7) solid solutions are studied in relation to the crystal structure. Q·f of suitable materials obtained by optimizing the sintering condition is in inverse proportion to the dielectric constant (ε r ). With increase of x, ε … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…Since in our research, an increase in the dielectric loss with an increase in temperature has been observed, therefore, it seems that the losses due to electrical conductivity are more dominant than those due to the relaxation effects [8,10]. The observed properties and their trends are similar to the trends observed in [4,8,9] and [12]. Decrease with frequency and increase with temperature is a general behavior observed in this category of ceramics.…”
Section: Loss Tangentsupporting
confidence: 79%
See 1 more Smart Citation
“…Since in our research, an increase in the dielectric loss with an increase in temperature has been observed, therefore, it seems that the losses due to electrical conductivity are more dominant than those due to the relaxation effects [8,10]. The observed properties and their trends are similar to the trends observed in [4,8,9] and [12]. Decrease with frequency and increase with temperature is a general behavior observed in this category of ceramics.…”
Section: Loss Tangentsupporting
confidence: 79%
“…With time, rare earth metals have been intentionally doped in the structure with the formula of Ba 2−x Sm 4+2x/3 Ti 8 O 24 [3] to improve their properties. These developments include the ceramics: Ba-R 2 O 3 -TiO 2 , (Zr,Sn)TiO 4 system, BaO-TiO 4 * E-mail: sukhleen2@yahoo.com titanium rich system, Ba (B 1/3 Ta 2/3 )O 3 (B = Mg, Zn) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the dielectric properties of Ba 6ࢬ3x R 8ࢪ2x Ti 18 O 54 solid solutions as a function of the composition x. 4,19 Similar results for Sm and Nd systems are reported by Negas et al 20 . The characteristic phenomenon is that Qɿf values varied non linearly as a function of composition, though e r and t f vary proportional to the composition.…”
supporting
confidence: 77%
“…However, those technologies have been struggled to fulfill the increasing demand for cost reduction, linearity and compactness. Recently, liquid crystals (LC) has become an interesting alternative to design tunable filters, because of its advantage in low power consumption, small cost and size reduction compared to other technologies [4]. Recent research on tunable resonators and filters based on LC are presented in [5][6][7][8][9][10], where various degrees of tunability have been quoted for various structures.…”
Section: Resultsmentioning
confidence: 99%
“…With time, rare earth metals were intentionally doped in this structure with structural formula Ba 2 2 x La 4 1 2x/3 Ti 8 O 24 [3] to have better properties. These developments included the ceramics: Ba-R 2 O 3 -TiO 2 , (Zr,Sn)TiO 4 system, BaO-TiO 4 titanium rich system, Ba (B 1/3 Ta 2/3 )O 3 (B 5 Mg, Zn) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%